A Review On Image Segmentation Techniques For MRI Brain Stroke Lesion - Mohd Saad, Norhashimah; Mohd Noor, Nor Shahirah; Abdullah, Abdul Rahim (Penerbit Universiti Teknikal Malaysia Melaka, 2021)
One of the major categories of brain disorders is known as stroke, which it can affect the entire body. The ability to recover from a stroke depends on the severity of the stroke and how quickly the patients receive the medical treatment. Conventionally, the diagnosis of brain stroke is performed manually by professional neuroradiologists during a highly subjective and time-consuming process. This paper reviewed the techniques for automatic magnetic resonance imaging of brain lesions segmentation. The proposed review is important to identify more robust and accurate technique in segmenting the brain stroke lesion for computer-aided diagnosis. This could be an opportunity for the medical and engineering to collaborate in designing a complete end-to-end automated framework in detecting and segmenting stroke lesions.